Ragam Dialog Deteksi Dini Gangguan Kesehatan Pada Pra Lansia - Roma Firmansyah; Sri Kusumadewi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The elderly who experience health complaints in 2020 reach half of the total elderly population in Indonesia. Decision support systems (SPKK) in medicine are used to diagnose diseases, but the problem that often occurs is that users have difficulty operating the system. This is because the information displayed is not in accordance with user needs and the lack of understanding of the principles of user interface (UI) and user experience (UX) in building attractive dialogue designs. Based on this situation, the prototype design was carried out using the user centered design (UCD) method and the doctor as the target user. The design of the prototype is adjusted to the stages of the diagnosis process such as the history prototype, the physical examination prototype, the supporting examination prototype and the diagnostic result prototype. There are 4 stages in the UCD approach, namely understanding the user context, determining user needs, design and evaluation. The evaluation process was carried out in 3 stages by 2 doctors with a direct interview process to get the desired dialogue design. After a redesign process that adjusted the evaluation results, the doctor finally stated that the variety of dialogues had fulfilled the information and needs of doctors to detect disorders in the elderly. The proposed prototype can be immediately implemented into the application program. For further research, especially systems that require physical examinations and supporting examinations for health problems.